BmCDK5 Affects Cell Proliferation and Cytoskeleton Morphology by Interacting with BmCNN in Bombyx mori - Yi Wei; Xiaolin Zhou; Peng Chen; Xia Jiang; Ziyi Jiang; Zhanqi Dong; Minhui Pan; Cheng Lu (Insects, 2022)
The ordered cell cycle is important to the proliferation and differentiation of living organisms. Cyclin-dependent kinases (CDKs) perform regulatory functions in different phases of the cell cycle process to ensure order. We identified a homologous gene of the Cyclin-dependent kinase family, BmCDK5, in Bombyx mori. BmCDK5 contains the STKc_CDK5 domain. The BmCDK5 gene was highly expressed in S phase. Overexpression of the BmCDK5 gene accelerates the process of the cell cycle’s mitotic period (M) and promotes cell proliferation; knocking out the BmCDK5 gene inhibited cell proliferation. Furthermore, we identified a protein, BmCNN, which can interact with BmCDK5 and represents the same express patterns as the BmCDK5 gene in the cell cycle phase and the spatial-temporal expression of B. mori. This study revealed that BmCDK5 and BmCNN play roles in promoting cell proliferation and regulating cytoskeleton morphology, but do not induce expression changes in microtubule protein. Therefore, our findings provide a new insight; the BmCDK5 gene has a regulatory effect on the cell cycle and proliferation of B. mori, which is presumably due to the interaction between BmCDK5 and BmCNN regulating changes in the cytoskeleton.